FLITARA: Culture-Based Interactive Flipbook Innovation to Improve Elementary Schools' Literacy in the Era of Society 5.0 - Putri, Deanova Wahyu Eksa; Sa'diyah, Zumrotus; Kunaifi, Aang; Mufidah, Zulfin Rachma; Syabiya, Nurita Fauzatin; Istiq'faroh, Nurul (Universitas Muhammadiyah Surakarta, 2025)
Literacy is a very important foundation in education, especially at the primary school level because these skills support students' cognitive, social and emotional development. This study aimed to present a flipbook-based learning solution as an interactive digital media in improving reading literacy skills through Nusantara culture materials. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, pretest and posttest tests, and validation from experts. The findings of this study indicate that the FLITARA medium achieved a very high validity rating and was empirically demonstrated to significantly enhance reading literacy and learning participation among third-year primary school pupils. Furthermore, this medium contributes to the internalisation of cultural values and the contextual development of pupils’ character. These results reinforce the proposition that the integration of digital technology grounded in local culture is not only pedagogically pertinent but also strategically vital for fostering national identity and advancing the attainment of sustainable education objectives.